An Empirical Comparison of Small Sample Distributions of Estimators of the First Order Autoregression - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1984)
This paper investigates the small sample distributions of estimators of the autoregressive parameter of the first order autoregression. Both conditional and exact processes are considered. The exact distributions are compared with Ochi's (1983) approximations and the Edgeworth approximations calculated using the algorithm given by Tse (1983). The latter approximations are found to be more accurate than Ochi's approximations